2005
DOI: 10.1038/sj.leu.2403866
|View full text |Cite
|
Sign up to set email alerts
|

Targeting an MMP-9-activated prodrug to multiple myeloma-diseased bone marrow: a proof of principle in the 5T33MM mouse model

Abstract: Multiple myeloma (MM) is an incurable B-cell cancer characterised by the monoclonal proliferation of tumour cells in the bone marrow (BM). It has been described that matrix metalloproteinases (MMPs) and especially MMP-9 is secreted by MM cells. In this study, we investigated the possibility to exploit MMP-9 activity to activate prodrugs and to target MM cells as a new tumour-specific therapy. Cleavage of the prodrug EV1-FITC by MMP-9 resulted in release of fluorescence which can be used as a measure of prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…MM cells were shown to constitutively produce MMP-9. 79,80 Similar results were observed with a VLA-4 (␣4␤1) inhibitory antibody 28 or with a selective antibody Natalizumab (Biogen Idec). 81 Similarly, P-selectin glycoprotein ligand-1 knockdown or inhibition by a small pan-selectin inhibitor (GMI-1070; Glycomimetics) showed significant inhibition of rolling and homing in vitro and in vivo.…”
Section: Circulation In the Peripheral Bloodsupporting
confidence: 67%
“…MM cells were shown to constitutively produce MMP-9. 79,80 Similar results were observed with a VLA-4 (␣4␤1) inhibitory antibody 28 or with a selective antibody Natalizumab (Biogen Idec). 81 Similarly, P-selectin glycoprotein ligand-1 knockdown or inhibition by a small pan-selectin inhibitor (GMI-1070; Glycomimetics) showed significant inhibition of rolling and homing in vitro and in vivo.…”
Section: Circulation In the Peripheral Bloodsupporting
confidence: 67%
“…Elevated levels of distinct MMP can be detected in serum of patients with advanced cancer, and their role as prognostic indicators in cancer has been widely examined [39]. Our results are consistent with Van Valckenborgh et al [40] who found that an anticancer compound (resveratrol) suppressed the activity of MMP-2 and MMP-9. It has been reported that a significant increase in MMP activity occurs in the bone marrow environment of patients with myeloma [41].…”
Section: Discussionsupporting
confidence: 95%
“…B-CLL cells expressed significant amounts of MMP-9, which was associated with increased invasion and lower patient survival rates [81,82]. One group has even developed a pro-drug that is activated by MMP-9 for MM therapy, as MM cells are known to overexpress MMP-9 [83]. Since levels of MMP-9, a mediator of tumor invasion, are increased in multiple types of hematological malignancies, it will be important to develop drugs that target MMPs.…”
Section: Cox-2/pge 2 Promotes Angiogenesis and Metastasismentioning
confidence: 99%